A REVIEW ON EXTRACTION SOLVENTS IN THE DISPERSIVE LIQUIDLIQUID MICROEXTRACTION - Tan, Yeong Hwang; Chai, Mee Kin; Wong, Ling Shing (The Malaysian Analytical Sciences Society, 2018)
Dispersive liquid-liquid microextraction (DLLME) is a novel sample preparation technique that has higher level of extraction efficiency by means of relying on microvolumes of solvents. It has gained considerable attention from researchers owing to several advantages such as its simplicity, shorter extraction time, lower cost and higher enrichment factor. In conventional DLLME, chlorinated solvents are widely used as the extraction solvents. Notwithstanding, most of these solvents are reportedly toxic and environmentally-unfriendly. Many related studies in recent years have focused on the use of nontoxic or low toxic extraction solvents and better practical procedures, which have helped improve the extraction efficiency. The aim of this review is to discuss the development of low toxic extraction solvent used recently in the DLLME. The possible improvement of extraction solvent from the green analytical chemistry perspectives is also discussed